Metode practice de pastorație a tinerilor în spațiul virtual reprezentat de televizor și internet - Fleșer, Alexandru (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
There should be a fairly close connection between the media and theology. The media often becomes a form of human personality. And the Church has this role. But the difference between the two is clear. The church is a real community, a unitary whole made up of believers understood as individuals and not as individuals. These people interact, see each other and communicate live with each other. Through the media it is not possible to form a real communion between people as in the Church. The Church recommends practical activities meant to be in total contradiction with the imaginary.